PERANAN DEWAN PERWAKILAN RAKYAT DALAM PEMBENTUKAN UNDANG-UNDANG MENURUT UNDANG-UNDANG DASAR NEGARA RI TAHUN 1945 SETELAH AMANDEMEN - Basrial Zuhri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The power to form laws after the amendment of the 1945 Constitution of the Republic of Indonesia, there has been a very significant change. This change makes the DPR's power stronger than the President. The power to make laws after the amendments rests with the House of Representatives. However, in joint discussions, the draft law requires the approval of the President. If the draft law does not get the President's approval, the draft law will be invalid. Thus, the power to make laws that is given to the DPR is canceled by the constitution or in other words, the constitution cancels itself. The DPD is also considered a legislative body, with a view to creating a two-chamber system in representative institutions. But in reality, the DPD in exercising its power is very weak. The weaknesses can be seen as follows: 1) DPD can only submit proposals for draft laws to the DPR, 2) The draft laws that can be proposed are limited to matters related to regional government as regulated by the constitution, 3) DPD participation in joint discussions at the DPR , if the draft law has not yet entered the stage of discussion with the President, 4) DPD cannot submit a draft law outside the national legislation program.Keywords: DPR, Law, 1945 Constitution, Amendment.